Rancang Bangun Sistem informasi Pengingat Status Paket Dengan Berbasis SMS Gateway Pada Logistik - Anggi syahputri; Edy Rahman Syahputra; Hasdiana (Universitas Harapan Medan, 2021)
Along with the rapid advancement of technology, it is only natural that companies engaged in logistics must provide fast and appropriate services so that customers feel comfortable and satisfied by using the company's services. One of them is access to information. Short Message Service (SMS) is one of the communication facilities found on mobile devices or fixed devices that use text format. The SMS Gateway application for this goods delivery information system allows registered customers and drivers to provide and access information quickly and easily. This SMS Gateway application is made using an API (Application Programming Interface) as a connecting tool between the modem and the laptop. This application is web-based using PHP programming with MySQL database. This development method uses the UML model. This application has been tested and the results are very useful for customers who use logistics delivery services.